Clinical and Laboratory Features of Scrub Typhus among Adult Patients with Acute Febrile Illness in Tak and Nakhon Phanom Provinces, Thailand, 2017–2020 - Adelaide F. Green; Betsy Cadwell; Emily Bloss; Nuttagarn Chuenchom; Supphachoke Khemla; Sumonmal Uttayamakul; Pongpun Sawatwong; Ornuma Sangwichian; Duangkamon Siludjai; Phanthaneeya Teepruksa; Beth Skaggs; Cecilia Y. Kato; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Scrub typhus (ST), caused by Orientia tsutsugamushi , is an underdiagnosed cause of acute febrile illness in Southeast Asia. Acute febrile illness surveillance data from febrile patients presenting to health facilities in two Thailand border provinces (Tak [north] and Nakhon Phanom [northeast]) were analyzed to estimate ST prevalence and describe clinical and epidemiological characteristics and risk factors. Scrub typhus cases were classified as confirmed (polymerase chain reaction-positive), probable (acute-to-convalescent rise in ELISA IgM/IgG plus ≥2 clinical features), or suspect (positive acute and convalescent sera results for anti-IgM/IgG or for patients with only one sera sample, positive acute or convalescent sera results for anti-IgM/IgG and ≥2 of these clinical features). All others were considered non-cases. The 75 ST cases were classified as confirmed (39) or probable (36). Scrub typhus prevalence was higher in Tak (6.9%; 95% CI: 4.8–9.4) than in Nakhon Phanom (1.3%, 95% CI: 0.6–2.3). Common symptoms included headache, fatigue, myalgia, and chills. Discharge diagnosis matched ST case designation 15% of the time. Approximately one-quarter ( n = 18) of patients were coinfected with another bacterium (15, 20%) or virus (3, 4%). Appropriate antibiotics were administered to 56% ( n = 9) of the 21% ( n = 16) of patients who received antibiotics before study specimen collections. Participants in Tak were 4.2 (95% CI: 2.2–8.2) or 4.5 (95% CI: 2.4–8.5) times as likely to test positive for ST if they visited the forest or contacted farm animals, respectively, within the past 30 days. Findings confirm the persistent burden of ST along Thailand’s borders. Targeted actions are needed to strengthen clinical management, access to diagnostics, and community-based prevention.